Small and Medium Scale Enterprises (SMEs) in Nigeria The Marketing Interface (Global Journal of Management and Business Research, 2013)
A business whether small or big, simple of complex, private or public is created to provide competitive prices. Business in Nigeria, has been classified as small, medium and large. In both the developed and developing countries, the government is turning to small and medium scale industries, as a means of economic development and a veritable means of solving problems. It is also a seedbed of innovations, inventions and employment. Presently in Nigeria, SMEs assist in promoting the growth of the country's economy, hence all the levels of government at different times has policies which promote the growth and sustenance of SMEs. Small scale industry orientation is part of the Nigerian history. Evidence abound in the communities of what successes our great grand parents, made of their respective trading concerns, yam barns, cottage industries, and the likes.
Keywords: SMES; marketing; business; needs; wants; products